2013
DOI: 10.1002/art.37837
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Accumulation of Prohibitin 1 in Osteoarthritic Chondrocytes Down‐Regulates PITX1 Expression

Abstract: Objective. To decipher the molecular mechanisms down-regulating PITX1 expression in primary osteoarthritis (OA).Methods. The functional activity of different PITX1 promoter regions was assessed by luciferase reporter assay. Tandem mass spectrometry coupled to protein sequencing was performed using nuclear extracts prepared from OA chondrocytes, in order to identify proteins bound to DNA regulatory elements. Expression analyses of selected candidate proteins were performed by real-time reverse transcriptionpoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…RNA extraction, cDNA synthesis, and real-time RT-PCR analysis were performed, as previously described [6]. Primer sequences are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA extraction, cDNA synthesis, and real-time RT-PCR analysis were performed, as previously described [6]. Primer sequences are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) using primary chondrocytes or C28/I2 cells and anti-E2F1 antibodies was performed, as previously described [6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence that PHB1 is a putative therapeutic target for treating IBD comes from the observations that adenovirus-directed administration by enema and nanoparticle-based colonic delivery of PHB1 effectively enhanced the levels of PHB1 at the surface of colonic epithelial cells and alleviated colitis induced by dextran sodium sulfate (Theiss et al, 2011). Picard et al (2013) recently demonstrated that PHB1 accumulates in the nucleus of osteoarthritic chondrocytes, where it represses the expression of the transcription factor PITX1, suggesting an involvement of PHB1 in the etiology of osteoarthritis.…”
Section: Phbs and Inflammatory Diseasesmentioning
confidence: 99%
“…The streptavidin-agarose pulldown assay is a useful and feasible approach for analyzing the binding of an array of proteins on DNA sequence [ 15 17 ]. The method combined with high-throughput proteomics can generate an effective screening system to indentify the novel DNA sequence binding proteins [ 18 21 ]. Using this technology, we previously discovered novel expression regulating mechanisms of carcinogenic genes COX-2 [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%